Genotyping of Human Papillomavirus (HPV) from Patients with Cutaneous Warts - Karam, Mohanad A.; Al-Hmudi, Hayder A. (Scientific Journal of Medical Research, 2019)
Objectives: To study the prevalence of genotyping of cutaneous human papillomaviruses in patients presented with skin warts in the Basrah and Missan provinces. Methods: A total of 152 cutaneous samples were collected from patients presented with skin warts in the Basrah and Missan provinces - Iraq during the period from October 2018 to May 2019. The researchers identified the samples genetically using the FAP PCR system followed by multiplex PCR and confirmed by DNA sequencing. Results: A 120 (78.95%) samples were positive according to the FAP PCR method, while a 131 (86.2%) samples were positive by using the multiplex PCR system; a 99 (75.6%) samples as single genotypes and 32 (24.4%) samples as multiple genotypes. HPV57, 1, 2, and 27 were the most detected HPV genotypes among cutaneous skin wart patients. Conclusion: HPV57, 1, 2, and 27 were the most common HPV genotypes associated with cutaneous skin warts in patients of the Basrah and Missan provinces. Multiple and single HPV genotypes were detected in the same sample.